Antigen levels of coagulation factor XII, coagulation factor XI and prekallikrein, and the risk of myocardial infarction and ischemic stroke in young women. (May 2014) - Siegerink, B.; Rosendaal, F. R.; Algra, A.
Summary Background High levels of activated protein–inhibitor complexes of the intrinsic coagulation proteins are associated with ischemic stroke (IS) but not with myocardial infarction (MI). This study was aimed at determining whether the antigen levels of coagulation factors (factor XII, FXII, and FXI and prekallikrein (PK) are associated with MI and IS, and whether this association is independent of levels of activated protein–inhibitor complexes. Patients and Methods The RATIO study included young women (< 50 years) with MI (N = 205) and IS (N = 175), and 638 healthy controls. Antigen levels of FXII, FXI and PK were measured and expressed as percentages of of those in pooled normal plasmas. Odds ratios (ORs) and corresponding 99% confidence intervals (CIs) were calculated for high levels (i.e. ≥ 90th percentile of controls) as measures of rate ratios. Results After adjustment for potential confounders, high levels of FXII antigen were not associated with MI risk or IS risk (ORMI 1.18, 99% CI 0.51–2.74; ORIS 1.03, 9% CI 0.41–2.55). High levels of FXI antigen were slightly associated with an increase in MI risk (ORMI 1.55, 9% CI 0.74–3.21), whereas there was a substantial association with IS risk (ORIS 2.65, 9% CI 1.27–5.56). PK antigen was slightly associated with MI risk but not with IS risk (ORMI 1.54, 9% CI 0.67–3.52; ORIS 0.90, 9% CI 0.35–2.33). All associations remained similar after adjustment for levels of protein–inhibitor complexes. Conclusion Increased levels of FXI antigen were associated with an increase in IS risk, whereas they showed only a marginal association with MI risk. FXII antigen and PK antigen levels were not substantially associated with MI risk and IS risk.